EKSISTENSI ASAS KONSENSUALISME DALAM PERJANJIAN KERJA SAMA BAGI HASIL PERKEBUNAN KELAPA BERDASARKAN KUHPERDATA - Purnama Sari; Muhammad Yadi Harahap (CV Rewang Rencang, 2024)
An agreement is an agreement between two or more parties. In Article 1320 of the Civil Code, it is stated that the conditions for the validity of an agreement are the existence of an agreement between the binding parties, the ability to make an agreement, a clear object, and a cause that does not conflict with the law. This research aims to ensure that the public understands how the principle of consensualism is applied in cooperation agreements for the production of coconut plantations in Sei Kepayang Village, as well as what the legal view is regarding the implementation of these agreements. The method used in this research is an empirical research method. This research is descriptive qualitative in nature, which aims to provide a comprehensive picture of the legal conditions that apply in society at a certain location and time. The author also conducted interviews with the community in Sei Kepayang village. The results of this research show that the principle of consensualism in the cooperation agreement for the production of coconut plantations is the sei kepayang study, an agreement that has agreed to work on and contain the results for two. However, the agreement for sharing the results of coconut plantations made by the Sei Kepayang Village community is generally implemented orally and is based on trust between the parties involved.